Data warehousing for dummies - Hammergren, Tom.; Simon, Alan R.; Safari eBooks (Hoboken, N.J. ; Indianapolis, Ind. : Wiley Pub., 2009)
Offers advice on designing and selecting data warehousing techniques, analysing data sources, selecting data to be stored, and facilitating the recall and distribution of information.
Description based on print version record.
Previous ed. entered under Alan R. Simon.
Includes index.
Keywords: Data warehousing; Electronic books